Tackling membrane fouling in microalgae filtration using nylon 6,6 nanofiber membrane - Bilad, M.R. (Academic Press, 2018)
Microalgae technology, if managed properly, has promising roles in solving food-water-energy nexus. The Achillesâ heel is, however, to lower the costs associated with cultivation and harvesting. As a favorable technique, application of membrane process is strongly limited by membrane fouling. This study evaluates performance of nylon 6,6 nanofiber membrane (NFM) to a conventional polyvinylidene fluoride phase inverted membrane (PVDF PIM) for filtration of Chlorella vulgaris. Results show that nylon 6,6 NFM is superhydrophilic, has higher size of pore opening (0.22 vs 0.18 Î¼m) and higher surface pore density (23 vs 18 pores/Î¼m2) leading to higher permeance (1018 vs 493 L/m2hbar) and better fouling resistant. Such advantages help to outperform the filterability of PVDF PIM by showing much higher steady-state permeance (286 vs 120 L/m2hbar), with comparable biomass retention. In addition, unlike for PVDF PIM, imposing longer relaxation cycles further enhances the performance of the NFM (i.e., 178 L/m2hbar for 0.5 min and 236 L/m2hbar for 5 min). Overall findings confirm the advantages of nylon 6,6 NFM over the PVDF PIM. Such advantages can help to reduce required membrane area and specific aeration demand by enabling higher flux and lowering aeration rate. Nevertheless, developments of nylon 6,6 NFM material with respect to its intrinsic properties, mechanical strength and operational conditions of the panel can still be explored to enhance its competitiveness as a promising fouling resistant membrane material for microalgae filtration. Â© 2018 Elsevier Ltd